RESPONS MASYARAKAT TERHADAP ADANYA GO-CAR DI KOTA MANADO - Poluan, Rival Arlando; Purwanto, Antonius; Goni, Shirley Y. V. I. (HOLISTIK, Journal Of Social and Culture, 2019)
Human life can not be separated with transport services, because humans need transportation services to meet the needs of his life. As the development of science and technology, used by companies to provide transportation services transportation services online. The company's Go-Jek, Grab, danUber now present in a society of the city of Manado. Go-Jek is transportation services using motor-driven online. This application can be downloaded via google play for users of android and apple's app store for the user. Applications Go-Jek also serves other online services such as GoCar, Go-Mart, Go-Shop, Go-Massage, Go-Clean, Go-Send, Bluebird, and GoGlam. One of the services available are Go-Car. Go-Car is an online community-based transport using the car as a medium transport. The car used is a kind of private vehicles like the agya, ayla, avansa, xenia, terios, rush and other personal vehicles. Go-Car give maximum service to the user Go-Carlike, friendly drivers, give discounts (discounts via go-pay), the circumstances, the availability of good car sweets and mineral water as well as affordability.Â  The presence technological advancement the taxi online existence can not be avoided. Taxi online community became the choice because it is considered better than conventional public transport. Both in terms of services, the comfort and certainty of the price for this is less perceived while using conventional transportation services. With the Go-Car in the town of Manado, passenger transport which have official permission from Dishub (Department of transportation) feel marginalized by continually increasing the online Go Transit-Car which, according to their perceptions of lowers the earnings of other transport driver because many passengers who switch to using the services of Go-Car.. Keywords: transportation, online, services